2015
DOI: 10.1111/sms.12479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different aerodynamic time trial cycling positions on muscle activation and crank torque

Abstract: To reduce air resistance, time trial cyclists and triathletes lower their torso angle. The aim of this study was to investigate the effect of lowering time trial torso angle positions on muscle activation patterns and crank torque coordination. It was hypothesized that small torso angles yield a forward shift of the muscle activation timing and crank torque. Twenty-one trained cyclists performed three exercise bouts at 70% maximal aerobic power in a time trial position at three different torso angles (0°, 8°, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Exercise intensity and torso angle have been shown to affect stroke volume, cardiac output muscle blood flow, deoxygenation and gross efficiency (Fintelman et al, 2016;Foster et al, 1999;Hettinga, Konings, & Cooper, 2016). Recently, Fintelman et al (2016) showed that lowering torso angle whilst cycling at 70% maximal aerobic power increased oxygen consumption, breathing frequency, minute ventilation and decreased gross efficiency. In speed skating, where athletes also adopt 'aggressive' aerodynamic positions with low torso angles, similar observations have been made.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intensity and torso angle have been shown to affect stroke volume, cardiac output muscle blood flow, deoxygenation and gross efficiency (Fintelman et al, 2016;Foster et al, 1999;Hettinga, Konings, & Cooper, 2016). Recently, Fintelman et al (2016) showed that lowering torso angle whilst cycling at 70% maximal aerobic power increased oxygen consumption, breathing frequency, minute ventilation and decreased gross efficiency. In speed skating, where athletes also adopt 'aggressive' aerodynamic positions with low torso angles, similar observations have been made.…”
Section: Discussionmentioning
confidence: 99%
“…This was identified in an early wind tunnel study conducted by Kyle and Burke [3] which led them to propose a three-tier hierarchy for reducing cycling resistance: (1) the position of the rider, (2) the geometry of the bicycle (or more generally cycling equipment), and (3) the methods for minimising the rolling resistance and drive-train friction losses. Although the biomechanics and physiological efficiency of cycling are outside the scope of this review, when optimising cycling performance, the power output and fatigue characteristics of cyclists must also be weighed up against any apparent gains in the aerodynamic performance through adjustment to position [47][48][49]. Any changes to rider posture must also be considered along with current UCI rulings on legal rider positions.…”
Section: Optimising Single-rider Aerodynamicsmentioning
confidence: 99%
“…Based on fundamental physics, these deceleration/acceleration phases are associated with a significant energy cost; however, the relative energy-cost contribution related to translational kinetic energy decreases during uphill running, because on inclines the braking forces at the foot plant decrease (Gottschall and Kram 2005). In cycling, the fluctuation in speed during the pedal cycle is lower than in running due to the continuous supply of power (Fintelman et al 2016;van Ingen Schenau et al 1990). The described energyexpenditure differences between the exercise modes result in a reduced biomechanical efficiency during running compared to cycling, which is the major factor explaining the lower GE during running.…”
Section: Discussionmentioning
confidence: 99%